2023
DOI: 10.20517/energymater.2023.60
|View full text |Cite
|
Sign up to set email alerts
|

Cathode materials in microbial electrosynthesis systems for carbon dioxide reduction: recent progress and perspectives

Su Hui,
Yujing Jiang,
Yuanfan Jiang
et al.

Abstract: Microbial electrosynthesis (MES) is an emerging technology that enables the synthesis of value-added chemicals from carbon dioxide (CO2) or inorganic carbon compounds by coupling renewable electricity to microbial metabolism. However, MES still faces challenges in achieving high production of value-added chemicals due to the limited extracellular electron transfer efficiency at the biotic-abiotic interfaces. To overcome this bottleneck, it is crucial to develop novel cathodes and modified materials. This revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 180 publications
0
1
0
Order By: Relevance
“…Several reductive pathways leading to distinct oxidation states of carbon (from C 2 O 4 2– to CH 4 ) have been documented in the scientific literature. Previous studies have shown that transition metal and p-block metal electrodes, such as Au, Ag, Cu, Pd, Pt, In, Sn, Hg, and Pb, are attractive candidates for CO 2 reduction reaction. Among them, Cu is the only metal catalyst that was found to produce considerable C1–C3 hydrocarbon products . Koper et al reported that bimetallic Pd–Pt alloy nanoparticles exhibit a very low onset potential and a high Faradaic efficiency for the selective reduction of CO 2 to HCOOH .…”
Section: Introductionmentioning
confidence: 99%
“…Several reductive pathways leading to distinct oxidation states of carbon (from C 2 O 4 2– to CH 4 ) have been documented in the scientific literature. Previous studies have shown that transition metal and p-block metal electrodes, such as Au, Ag, Cu, Pd, Pt, In, Sn, Hg, and Pb, are attractive candidates for CO 2 reduction reaction. Among them, Cu is the only metal catalyst that was found to produce considerable C1–C3 hydrocarbon products . Koper et al reported that bimetallic Pd–Pt alloy nanoparticles exhibit a very low onset potential and a high Faradaic efficiency for the selective reduction of CO 2 to HCOOH .…”
Section: Introductionmentioning
confidence: 99%